Preliminary Reflection on Basic Problematics of National Public Infrastructure Financing in Indonesia - Ria Asih Aryani Soemitro; Hitapriya Suprayitno (Journal of Infrastructure & Facility Asset Management, 2020)
Furnishing adequate national public infrastructure is an obligation for the government. Financing the infrastructure is not an easy problem. The main problem are that the NREB cannot finance the investment cost and the NREB capacity is not enough to finance he whole infrastructure needed. If in general the public infrastructure is merely a cost, there are certain infrastructure which can generate revenue. Meanwhile the GDP is far higher then the NREB. So, thinking involving private fund in public infrastructure financing is logical. Thus public infrastructure financing should be a mixture of public and private fund. The activity involving the Private Sector must be in an Attractive Comercial Activity. Thus preferably for revenue generator infrastructure. Revenue can be generated in various form. The basic idea of solutions can be grouped into fully financed by public budget, by a mixture of public private fund, and by fully private financed. Each group has its owned characterisitcs and derivative solution.